Leveling Up Language Learning: The Role of Web-Based Educational Games in Private English Instruction in Surakarta - Maulida, Nimas Ayu Nawal; Prastiwi, Yeny; Wijayanto, Agus; Hidayat, Nur; Sutopo, Anam (Universitas Muhammadiyah Surakarta, 2025)
The rapid digitalization of education has positioned web-based games as powerful tools in language learning. However, while their use in traditional classrooms is well-researched, their application within the burgeoning private English tutoring sector in Indonesia remains significantly underexplored. This study addressed this gap by examining the implementation, perceptions, and outcomes of using British Council educational games in private English instruction in Surakarta, Indonesia. The research aimed to understand how tutors adapt these games for individual needs, explore student experiences in a one-on-one context, and identify the unique challenges and benefits that differ from classroom settings. Adopting a qualitative research design, this study employed in-depth case studies of three private English tutors and nine of their students in Surakarta. Data collection utilized semi-structured interviews, classroom observations, and document analysis to provide rich, contextual insights into the implementation and experiences of game-based learning in personalized instruction environments. Data was analyzed using thematic analysis to identify patterns, themes, and categories that emerged from participants' experiences. The findings revealed valuable insights into effective pedagogical strategies. Tutors were found to use selective integration and real-time adaptation, while students reported high motivation due to personalized challenges and a low-pressure environment. These findings inform tutor training programs and provide evidence-based guidance for leveraging educational technology in the private tutoring industry.